Integration of GIS and Universal Soil Loss Equation (USLE) for Soil Loss Estimation in a Himalayan Watershed - Sarvesh Palria2; Akhtar Alam3, Ashaq Hussain SheikhÂ¹, (Recent Research in Science and Technology, 2011)
In order to assess soil erosion at watershed scale Universal Soil Loss Equation (USLE) erosion model has been used on IEL7 watershed of Lidder Catchment in Himalayan Region. Erosion calculation requires huge amount of information and data, usually coming from different sources and available in different formats and scales. Therefore GIS was used, which helped considerably in organizing the spatial data representing the effects of each factor affecting soil erosion. The factors that most influence soil erosion are linked to topography, vegetation type, soil properties and land use/cover. Average annual soil losses were calculated by multiplying five factors: R; the erosivity factor, K; the soil erodibility factor; LS, the topographic factor; C, the crop management factor and P; the conservation support practice. The annual soil loss predictions range between 0 and 61tons ha-1. Average soil loss was highest (26 tons ha-1 year-1) in agriculture area and lowest soil loss rate was found in forest area (0.99 tons ha-1 year-1). For horticulture and plantation the soil loss rates were 1.47 and 5.39 tons ha-1 year-1 respectively. For pasture, fallow and scrub the soil loss rates were 25.47, 28.39 and 35.76 tons ha-1 year-1 respectively.